Improving the optical efficiency of white light-emitting diodes based on phosphor-in-glass by a dual-layer remote phosphorus structure with the application of LiLaO2:Eu3+ and CaSO4:Ce3+, Mn2+ - Phan Xuan Le; Le Tien (Institute of Advanced Engineering and Science, 2021)
While the remote phosphor structure is not an appropriate solution for WLED color uniformity, it is more advantageous for the luminous output of WLED than the conformal phosphor or in-cup phosphor structure. Acknowledging the ability of the remote phosphor structure, many studies have been carried out to surmount the color quality disadvantage of this structure. A dual-layer remote phosphor configuration is proposed in this research paper to acquire better color quality for WLEDs through heightening the color rendering index (CRI) and the color quality scale (CQS). The color temperature of the WLED packages this study is 8500 K. By inserting a layer of green CaSO4:Ce3+,Mn2+ or red LiLaO2:Eu3+ phosphor on the yellow YAG:Ce3+ phosphor layer, the phosphor structure configuration can be constructed. Then, to get the best color quality, the concentration of added phosphor LiLaO2:Eu3+ would be changed. The findings showed the rise of CRI and CQS along with the LiLaO2:Eu3+, which implies the influence of LiLaO2:Eu3+ to the growth of red light components within WLEDs packages. The greater the concentration of LiLaO2:Eu3+ is, the more the CRI and CQS increase. Meanwhile, the luminous flux gains from the green phosphor CaSO4:Ce3+,Mn2+. Nevertheless, the luminous flux and color quality would decrease if the concentrations of both red LiLaO2:Eu3+ and green CaSO4:Ce3+,Mn2+ phosphors reach a certain corresponding level. Centered on the Mie-scattering theory and the law of Lambert-Beer, this result is illustrated. The findings in this research are vital references for manufacturing WLEDs with higher white light performance.